Oman’s Islamic Banking Performance amidst Covid-19 Outbreak: Prospects and Challenges - Mihajat, Muhammad Iman Sastra (IAIN Surakarta, 2021)
Covid-19 pandemic forced Islamic banking in Oman to slow down and to change strategies adapting to the current situation. The Covid-19 outbreak has raised various challenges for Islamic banking. In order to maintain the sustainable growth of the industry, stakeholders of Islamic banking should strive collectively to solve these challenges. Nevertheless, Islamic banking was able to maintain and manage capital and liquidity buffers. The growth for 2021 is expected to remain stable for at least a single-digit growth. However, there would be asset-quality and profitability pressure for Islamic banks within the Sultanate of Oman. This paper highlights the performance of Islamic banking in Oman amid the Covid-19 outbreak. This paper demonstrates that the industry merely recorded a single-digit growth compared to the last seven years at double-digit growth due to the pandemic. The paper further delineates on the prospects and challenges of Islamic Banks Entities (IBEs). It also suggests some practical solutions for survival. This paper contributes to providing an alluded picture of the current conditions and situation of Islamic banks in Oman as well as insights to deal with the challenges to enhancing the banking performances during the Covid-19 outbreak.Â